What human trust networks reveal about cognitive mechanisms of group cohesion in primates. - Acedo-Carmona, Cristina; Gomila, Antoni (Cambridge University Press, 2025)
Drawing on our previous work on human trust networks, we provide further evidence of how group structure can foster group cohesion. But this work also raises doubts about two central tenets of the target paper: 1) the role assigned to cognitive abilities in group cohesion and stabilization; and 2) the emphasis on group size as the critical variable.
https://openpolicyfinder.jisc.ac.uk/id/publication/1419
Keywords: Primates - Conducta; Dinámica de grupos; Confianza - Aspectos sociales; Trust networks; Cognition; Primates; Group cohesion